Local Governments: Catalysts or Barriers to Sport Event Tourism Development in Romania? - Tunde GAL (Communications of International Proceedings, 2021)
The organization of a sport event, depending on its size, can leave a significant mark on a host region, with an impact on the economy, the environment, and the well-being of the local community. This impact varies with the size of the event, which can range from a small community sports contest to a mega-event like the Olympic Games. The objective of this paper is to investigate the sport event tourism development in Romania focusing on outdoor sport events which target active participants, analysing sport participation rates, the exploitation of sport tourism destinations in Romania, the cooperation rate between local government and sport event organizers, and also aspects on how the pandemic changed this market recently. The research methodology is exploratory, involving the analysis of the available statistical data to delineate Romania's place at the EU level, and a semi-structured survey to trace the development of the Romanian sport event tourism market through the lens of event organizers. Research results show that Romania's accession to the European Union brought several positive changes in the sport tourism market, the number of different sport events attracting local and international tourists increased until the pandemic period, and it is quickly recovering with the help of the vaccine, but taking in consideration the existing natural resources, sport participation, the quality and quantity of the existing sport infrastructure and therefore the exploitation of opportunities is still relatively low. This is in many cases due to a lack of communication, involvement, and strategic thinking from the local government.
Keywords: Sport event; sport tourism; active sport tourist; Romania; local government